Applied sciences in graphic communication and packaging : proceedings of 2017 49th Conference of the International Circle of Educational Institutes for Graphic Arts Technology and Management & 8th China Academic Conference on Printing and Packaging /: proceedings of 2017 49th Conference of the International Circle of Educational Institutes for Graphic Arts Technology and Management & 8th China Academic Conference on Printing and Packaging. (2018) - Unknown
No abstract available